2016
DOI: 10.1007/s00221-016-4730-5
|View full text |Cite
|
Sign up to set email alerts
|

Cortical activity modulations underlying age-related performance differences during posture–cognition dual tasking

Abstract: To date, no systematic research investigating cortical correlates of performance changes in dual tasking has been reported in the elderly population. Thus, we monitored whole-scalp cortical activations (EEG) during both single task and posture-cognition dual tasking with the main goal of understanding cortical activity modulations underlying age-related differences on posture-cognition dual tasking conditions. Postural and cognitive data analyses showed that elderly people had decreased cognitive performance e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
39
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 86 publications
6
39
1
3
Order By: Relevance
“…The finding well agrees with studies used attention tasks (Gundel and Wilson, 1992;Ergenoglu et al, 2004) and visual n-back WM tasks (Gevins et al, 1997;McEvoy et al, 2001). However, other studies reported an increase in alpha power with increased WM load (Jensen et al, 2002;Herrmann et al, 2004;Johnson et al, 2011, Ozdemir et al, 2016. The discrepancy between the results may be accounted for by differences in WM tasks, experimental conditions and, in some cases, individual differences of participants.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…The finding well agrees with studies used attention tasks (Gundel and Wilson, 1992;Ergenoglu et al, 2004) and visual n-back WM tasks (Gevins et al, 1997;McEvoy et al, 2001). However, other studies reported an increase in alpha power with increased WM load (Jensen et al, 2002;Herrmann et al, 2004;Johnson et al, 2011, Ozdemir et al, 2016. The discrepancy between the results may be accounted for by differences in WM tasks, experimental conditions and, in some cases, individual differences of participants.…”
Section: Discussionsupporting
confidence: 86%
“…The majority of EEG studies have reported changes in spectral power of theta and alpha frequency bands during task performance. Theta power is usually enhanced in a variety of tasks with high WM demands (Gevins et al, 1997;2000;Smith et al, 1999;McEvoy 2001;Deiber et al, 2007;Itthipuripat et al, 2013;Gärtner et al, 2014;Ozdemir et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Doron et al (2010) using diffusion imaging tractography showed also that prefrontal connections to the cerebellum are involved in the control of eye movements. Interestingly, studies investigating cortical modulation activity during dual task in healthy young subjects reported increased activities in parietal and frontal structures when the secondary task requests cognitive activities (Jensen and Tesche, 2002; Ozdemir et al, 2016; Rosso et al, 2017). In light of our results, we hypothesized these neural structures could be impaired in children with neurodevelopmental disorders leading to the difficulties to focus their attention on the secondary task in dual task conditions.…”
Section: Discussionmentioning
confidence: 99%